Electrochemotherapy for the treatment of primary basal cell carcinoma; A randomised control trial comparing electrochemotherapy and surgery with five year follow up. Issue 5 (May 2020) - Clover, A.J.P.; Salwa, S.P.; Bourke, M.G.; McKiernan, J.; Forde, P.F.; O'Sullivan, S.T.; Kelly, E.J.; Soden, D.M.
Abstract: Basal cell carcinoma (BCC) are the commonest cutaneous malignancy and incidence continues to increase. There is a need to expand the therapeutic toolbox to increase options for patients that are unsuitable for or unwilling to undergo the current therapies. Electrochemotherapy (ECT) is a technique where cells are temporarily permeabilized after exposure to a brief pulsed electrical field and combined with low dose chemotherapeutics to ablate malignancies. It is a simple technique causing minimal damage to the surrounding healthy tissue and has the potential to avoid the need for complex reconstruction. ECT is an established treatment for skin metastases but its role as a primary treatment modality is not demonstrated. A prospective randomised control trial evaluating ECT against the gold standard of treatment, Surgery, was performed for patients with primary BCC and patients followed for 5 years. All lesions treated with ECT (n = 69) responded although 8/69 (12%) needed a second treatment to ensure a complete response. All surgical lesions (n = 48) showed histological evidence of complete excision with 2/48 (4%) undergoing a second excision. At 5 years, in the surgical arm there was no evidence of recurrence in 39/40 (97.5%) lesions with 1/40 (2.5%) confirmed recurrence. In the ECT arm there was no evidence of recurrence in 42/48 lesions (87.5%). There was 5 confirmed recurrences. These groups show statistical equivalence in this non inferiority study design (p = 0.33). ECT is an effective and durable treatment option for primary BCC and should be considered as part of the armamentarium of options available.